1040 Evaluation of Three Resuscitation Protocols in Hypovolemic Shock Using Microcirculation Analysis in an Animal Model. (October 2012) - Gonzalez, R; Urbano, J; Solana, MJ; Botran, M; García, A; López-Herce, J; López, J
Abstract : Background and Aims: Ideal treatment of hypovolemic shock is not well established yet. Comparison of different treatments usually focuses on global haemodynamics. Our aim was to study if microcirculation analysis shows differences between three different resuscitation treatments. Methods: After sedation, relaxation and mechanical ventilation, hypovolemic shock was induced with controlled bleed (30ml/kg) in 17 two-month-old piglets. After 30 minutes pigs randomly received treatment with either normal saline (NS) 30 ml/kg, Albumin 5% plus Hypertonic 3% Saline (AHS) 15 ml/kg or Albumin 5% plus Hypertonic 3% Saline plus a bolus of Terlipressin 20 µg/kg (TAHS). Microcirculation was assessed following international consensus recommendations. Perfused vessel density (PVD), microvascular flow index (MFI) and heterogeneity index (HI) where determined at basal, post bleeding and after treatment. Results: After treatment PVD and MFI where higher in AHS and TAHS groups than NS group and HI values were lower, but differences between the three treatment groups were not statistically significant. Median values for PVD were 13.0±0.9 (NS); 14.0±1.8 (AHS) and 14.0±1.9 (TAHS) (p=0, 539). MFI median values were 2.47±0.29 (NS); 2.75±0.23 (AHS) and 2.67±0.19 (TAHS) (p=0, 204). HI median values were 0.43±0.23 (NS); 0.22±0.20 (AHS) and 0.32±0.21 (TAHS) (p=0, 316). Conclusions: After treatment there were no significant differences between the three treatments in none of the three microcirculation parameters. There are no significant differences in microcirculation analysis between several treatments of hypovolemic shock.